2005
DOI: 10.1124/mol.105.013144
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Synthesis and Degradation in the Post-Transcriptional Regulation of Rat Multidrug Resistance-Associated Protein 2 (Mrp2, Abcc2)

Abstract: Multidrug resistance-associated protein 2 (Mrp2, Abcc2), an organic anion transporter present in the apical membrane of hepatocytes, renal epithelial cells, and enterocytes, is postulated to undergo post-transcriptional regulation. We hypothesized that Mrp2 protein undergoes altered rates of protein synthesis or degradation consistent with different Mrp2 protein expression. We analyzed Mrp2 synthesis, expression, and degradation in control female, 19-and 20-day pregnant, and pregnenolone-16␣-carbonitrile (PCN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…siRNAs have already been used to reverse multidrug resistance in human cancer cell lines due to overexpression of P-glycoprotein (19), MRP1 (12), MRP2 (21), MRP4 (31), or BCRP (30). The incomplete decreased expression observed here (about 70%) is in line with what is commonly observed with this type of approach for other transporters (12,21,41) and could be accounted for by the very large amount of protein present (41) and/or its long half-life (as is the case for other transporters, such as P-glycoprotein [26], MRP1 [1], or MRP2 [16]), as well as the short half-life of the siRNAs.…”
Section: Discussionsupporting
confidence: 70%
“…siRNAs have already been used to reverse multidrug resistance in human cancer cell lines due to overexpression of P-glycoprotein (19), MRP1 (12), MRP2 (21), MRP4 (31), or BCRP (30). The incomplete decreased expression observed here (about 70%) is in line with what is commonly observed with this type of approach for other transporters (12,21,41) and could be accounted for by the very large amount of protein present (41) and/or its long half-life (as is the case for other transporters, such as P-glycoprotein [26], MRP1 [1], or MRP2 [16]), as well as the short half-life of the siRNAs.…”
Section: Discussionsupporting
confidence: 70%
“…There was a clear parallel between the protein content of Abcc2 and the transport activity, suggesting that cPKC activation induces a decrease in the transport activity of Abcc2 as a result of decreased protein content of Abcc2 on BBM surface. It is reported that the half-life of Abcc2 in the canalicular membrane is as long as 27 h (Jones et al, 2005). If Abcc2 in the BBM fraction is as stable as that in the bile canalicular membrane, the decrease in BBM observed without a change in the total amount of Abcc2 is probably caused by accelerated internalization rather than impaired trafficking of newly synthesized molecules to the BBM.…”
Section: Discussionmentioning
confidence: 99%
“…The present data are in accordance with a recent report showing that Mrp2 is not induced by PCN in mouse liver. However, it has been reported that Mrp2 may be regulated in rat liver at a post-translational step (Gerk and Vore, 2002;Johnson and Klaassen, 2002;Jones et al, 2005). Mdr1a is induced in mouse small intestine by PCN, but not in either liver or kidney.…”
Section: Discussionmentioning
confidence: 99%